Effects of surface morphology on Ag crystallite formation in screen-printed multi-crystalline Si solar cells. (15th June 2021) - Han, Hyebin; Choi, Dongjin; Jeong, Sujeong; Kang, Dongkyun; Park, HyunJung; Bae, Soohyun; Kang, Yoonmook; Lee, Hae-Seok; Kim, Donghwan
Abstract: The electrode collects electrons produced by a solar cell. Ag crystallites generated during front electrode formation play an important role in transferring electrons from the emitter to the Ag finger. Previously, the formation mechanism of Ag crystallites and the various factors influencing Ag crystallite formation have been studied, including the effect of surface morphology on Ag crystallite formation. The glass coverage varies with the texture of the Si surface, and thus the degree of exposure of the Si surface varies correspondingly. When the Si surface is exposed, direct contact is achieved, and contact resistance is improved. However, the effect of surface morphology on the Ag crystallites formed on the Si surface under the glass layer has not yet been studied. The effect of surface morphology on Ag crystallite formation is presented in this work. Two multi-crystalline Si wafers with different surface morphologies were compared. The first multi-crystalline Si wafer was textured using metal-catalyzed chem ical etching (MCCE). The second multi-crystalline Si wafer was textured by MCCE followed by reactive ion etching. Wafers with sharper textures had lower series resistances, higher fill factors, and a large amount of Ag crystallites. Ag crystallites primarily formed at the tips of the texture. To analyze the effect of surface morphology, the surface electron concentration was confirmed by simulation. Electron concentration at the tip was proportional to the sharpness of the tip. Therefore, when the firing process is performed at the same temperature, wafers with sharper tips are expected to exhibit better electrode characteristics. Highlights: The amount of Ag formed on Si surface varies depending on the morphology. More Ag crystallites are generated at the tip than in the valley or on the surface. Sharper tips on the surface exhibit higher electron concentrations. Electrons on the surface participate in the Ag formation reaction.